Use of small streams by juvenile Atlantic salmon, Salmo salar, and brown trout, Salmo trutta, in the Ponoi River, Russia - Crabbe, Sarah Jill (University of Guelph, 2000)
Movements of juvenile Atlantic salmon ('Salmo salar') and brown trout ('Salmo trutta') between the Ponoi mainstem spawning areas and three small tributaries were investigated. Juveniles of both species use these tributaries as rearing habitat. Their movements between the mainstem and tributaries were monitored using trap-fences. Spatial separation of the two species and their degree of movement once in a small stream were also investigated. Juvenile salmon in the tributaries were younger (age-1+ and 2+) and grew poorly after moving compared with the group remaining in the mainstem. The movement may be in response to predation or intraspecific competition within the natal sites. Juvenile salmon and trout exhibited relative spatial separation within the tributaries and most fish showed little movement once in the new habitat. It appears that juvenile salmon exploit the small tributaries for only one season while brown trout may remain in the tributaries until maturity.